Internal anomalies in thalidomide embryopathy: results of imaging screening by CT and MRI. Issue 11 (November 2016) - Tajima, T.; Wada, T.; Yoshizawa, A.; Masuda, T.; Okafuji, T.; Nakayama, T.; Hasuo, K.
Abstract : Aim: To examine the prevalence and detailed radiological findings of internal anomalies in thalidomide embryopathy (TE). Materials and methods: Whole-body image screening for internal anomalies using unenhanced whole-body computed tomography (CT) and head magnetic resonance imaging (MRI) was performed in 22 patients (13 women and nine men; mean age, 49 years; range, 47–51 years) with TE. Results: Among the 22 patients with TE, internal anomalies were detected in 19 (86.4%): anomalies of the auditory organ in 10 (45.5%), anomalies of the vascular system in six (27.3%), agenesis of the gallbladder in six (27.3%), hypoplasia or aplasia of the 7th or 8th cranial nerves in five (22.7%), block vertebrae in five (22.7%), fusion of the left lobe and quadrate lobe of the liver in three (9.1%), and others in five (22.7%), respectively. Conclusion: In addition to limb defects or hypoplasia, various internal anomalies can be detected at a high incidence in TE using CT and MRI. Understanding these characteristic radiological findings may help radiologists detect a wide range of radiological findings of internal anomalies associated with TE. Highlights: In patients with thalidomide embryopathy, various internal anomalies are detected by CT and MRI. In the abdominal region, unenhanced CT demonstrated agenesis of the gallbladder in 27.3%. Fusion of the left lobe and quadrate lobe of the liver was newly detected in three patients. Block vertebrae were seen in 23% of patients with TE in our study.